2018
DOI: 10.1158/1078-0432.ccr-17-3401
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Genomic and Immunophenotypic Classification of Pancreatic Cancer Reveals Three Distinct Subtypes with Prognostic/Predictive Significance

Abstract: Current clinical classification of pancreatic ductal adenocarcinoma (PDAC) is unable to predict prognosis or response to chemo- or immunotherapy and does not take into account the host reaction to PDAC cells. Our aim is to classify PDAC according to host- and tumor-related factors into clinically/biologically relevant subtypes by integrating molecular and microenvironmental findings. A well-characterized PDAC cohort ( = 110) underwent next-generation sequencing with a hot spot cancer panel while next-generatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
167
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(186 citation statements)
references
References 60 publications
13
167
0
Order By: Relevance
“…44 Regarding the presence of any potential specific driver genes in MSI/dMMR PDAC, we found a bi-univocal correspondence regarding genes belonging to the JAK/STAT pathway and those of KMT2 family. Indeed, these have been described as frequently mutated in MSI/dMMR cancers of different extrapancreatic sites 45 46 ; the review of all molecular data of MSI/ dMMR PDAC showed the involvement of the JAK/STAT pathway also in MSI/dMMR PDAC, given that the paper by Wartenberg et al, 39 reported a higher mutation rate of JAK3 specifically in this genetic subgroup (3/5 MSI/dMMR cases vs 4/105 microsatellite-stable PDAC, p<0.01, Fisher's exact test; all these cases were KRAS mutated), and in the paper by Singhi et al, two of the three reported MSI/dMMR PDAC harboured a JAK1 mutation (2/3 MSI/dMMR PDAC vs 0/608 microsatellitestable PDAC with actionable targets, p<0.01, Fisher's exact test). 44 Furthermore, we found that alterations affecting the KMT2 family were involved as well, since 3/3 MSI/dMMR cases described by Singhi et al harboured KMT2 mutations (two cases with KMT2D and one case KMT2C mutation; 3/3 KMT2 mutated MSI/dMMR PDAC vs 32/608 KMT2 mutated microsatellite-stable PDAC with actionable targets, p<0.01, Fisher's exact test; the MSI/dMMR and KMT2 mutated cases were KRAS wild type).…”
Section: Resultsmentioning
confidence: 99%
“…44 Regarding the presence of any potential specific driver genes in MSI/dMMR PDAC, we found a bi-univocal correspondence regarding genes belonging to the JAK/STAT pathway and those of KMT2 family. Indeed, these have been described as frequently mutated in MSI/dMMR cancers of different extrapancreatic sites 45 46 ; the review of all molecular data of MSI/ dMMR PDAC showed the involvement of the JAK/STAT pathway also in MSI/dMMR PDAC, given that the paper by Wartenberg et al, 39 reported a higher mutation rate of JAK3 specifically in this genetic subgroup (3/5 MSI/dMMR cases vs 4/105 microsatellite-stable PDAC, p<0.01, Fisher's exact test; all these cases were KRAS mutated), and in the paper by Singhi et al, two of the three reported MSI/dMMR PDAC harboured a JAK1 mutation (2/3 MSI/dMMR PDAC vs 0/608 microsatellitestable PDAC with actionable targets, p<0.01, Fisher's exact test). 44 Furthermore, we found that alterations affecting the KMT2 family were involved as well, since 3/3 MSI/dMMR cases described by Singhi et al harboured KMT2 mutations (two cases with KMT2D and one case KMT2C mutation; 3/3 KMT2 mutated MSI/dMMR PDAC vs 32/608 KMT2 mutated microsatellite-stable PDAC with actionable targets, p<0.01, Fisher's exact test; the MSI/dMMR and KMT2 mutated cases were KRAS wild type).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of tumor budding in surgical samples has been clearly described to be related to advanced pT classification, lymphatic invasion, decreased disease-free and overall survival (DFS; OS) [13]. A correlation between the grade of tumor budding and the immune system invasion has been reported, with high grade of tumor budding being associated with FOXP3+ regulatory T cells invasion and worse prognosis [19].…”
Section: Not Investigated In Clinical Studiesmentioning
confidence: 99%
“…Deletion of CDKN2A and KRAS mutations were reported as adverse prognostic markers throughout a plethora of diverse malignancies . Thus, poor prognosis associated with CDKN2A deletion and KRAS activation appears as a recurrent feature of a broad spectrum of malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…12 Deletion of CDKN2A and KRAS mutations were reported as adverse prognostic markers throughout a plethora of diverse malignancies. [21][22][23][24][25][26][27][28][29] Thus, poor prognosis associated with CDKN2A deletion and KRAS activation appears as a recurrent feature of a broad spectrum of malignancies. As CUP may arise from any organ site, it is plausible that these negative prognostic effects observed in other cancer entities are also reflected in CUP.…”
Section: Discussionmentioning
confidence: 99%